SISTEM PEMILIHAN RUMAH KOS TERBAIK DI SEKITAR UNHASY DENGAN METODE MULTI ATTRIBUTE UTILITY THEORY (MAUT) BERBASIS WEB - Hidayatullah, Arif; Kadek Dwi Nuryana, I; Andriani, Anita (Inovate, 2019)
Boarding house is temporary house rent by a settled foreigner or someone who stays a way from home. Someof unhasy students from outside the city find some difficulties to get information about the boarding house, they haveto come and compare it. It makes them confused to select the best boarding house. Therefore, it is necesssary to presenta system on selecting a boarding house in order to help the students. The system implements MAUT method with several criteria related to finding the best boarding house. Thesuperiority of the MAUT method is able to process data from multiple criteria which have different attributes. Asanother DSS method, MAUT is only able to solve the problem of semi-structured and non-structured.The system work by searching the result of total evaluation on every boarding house based on the determinedcriteria and alternative clasification. As the result, the system shows the best boarding house to be recomended. the comparison between system and manual calculation gets 100 % accuration. This proves that the MAUT method hasbeen successfully applied to the system, and able to give recomendation the best boarding house based on the specificcriteria above.Keyword : boarding house, decision supporting system, MAUT, Information System